Injury incidence and characteristics for elite, male, artistic USA gymnastics competitions from 2008 to 2018 - Kruse, D. W.; Nobe, A. S.; Billimek, J. (British Journal of Sports Medicine, 2021)
Objectives: To determine the injury incidence and characteristics for elite, male, artistic USA gymnasts during gymnastics competitions, held in the USA, from 2008 to 2018.